Conceptualization of Empowerment of Ordained Women in Leadership in the Wesleyan Tradition as Exhibited in the Methodist Church in Kenya - Kinoti, Mary (International Journal of Professional Practice, 2019)
Mainstreaming and empowering women in leadership is not a challenge only in politics as witnessed in Kenya but also in church and corporate leadership. Gender inequality is prevalent in the Church resulting to women underrepresentation. That is in spite of the fact that ordained women’s participation in all levels of leadership is central to the ministerial work of the church. The study set out to examine how Methodist Church of Kenya (MCK) empowers ordained women to participate in leadership of the church and apparently achieve its mission. In addition, the study sought to establish opportunities and challenges facing the ordained women as they struggle to participate in the highest levels of leadership. The study used mixed methods though it was largely qualitative. Purposive sampling was done and out of a total population of eighty-five (85) ordained women ministers, 30% (25 women) were sampled within different levels of leadership in the MCK. Open ended questionnaires and interviews were conducted to collect data. The data was analysed to quantify the participation of ordained women ministers in MCK leadership and also their effectiveness as ministers of the word. Results were then presented in tables and charts. The study found out that women were not actively taking up leadership positions in the church compared to the male colleagues. The study concluded that the church has put in place mechanisms to ensure women ministers are trained and equipped and therefore their need to be more aggressive in utilizing the opportunities.